Trend in the use of biological drugs in pediatric patients with immune-mediated inflammatory diseases: Insight from the large-scale Italian VALORE project - Chiara Bellitto; Ylenia Ingrasciotta; Federica Soardo; Andrea Spini; Luca L’Abbate; Giorgia Pellegrini; Clément Mathieu; Massimo Carollo; Marco Tuccori; Olivia Leoni; Arianna Mazzone; Domenica Ancona; et al. (Pharmacological Research)
Real-world data on biological drug use in pediatric patients with immune-mediated inflammatory diseases (IMIDs) are scarce. This retrospective, population-based, cohort study aimed to provide an overview of biological drug use among children and adolescents with IMIDs from 2010 to 2023 using the Italian VALORE distributed database network. As secondary aim, potential of such a network for evaluating the risk of serious infections related to biological drugs in pediatrics was investigated. The yearly prevalence of use of biological drugs in IMID pediatric patients was calculated. Among incident users, persistence to adalimumab, etanercept, infliximab, golimumab, tocilizumab, secukinumab, and abatacept was measured. A sample power analysis to estimate the person-years of exposure required to investigate the association with the risk of serious infection and individual biological drug was performed. The yearly prevalence of biological drug use increased over time (+427.3 %), and it was consistently higher among females than males and among 12–17-year-olds than younger children. A total of 6222 incident biological drug users were identified, with a median follow-up of 3.8 years, and juvenile idiopathic arthritis (JIA, 35.9 %) and inflammatory bowel diseases (IBDs, 35.9 %) were the most common indications for use. After one year from the treatment start, more than 70 % of JIA patients using either adalimumab or etanercept were still on treatment, while persistence rates in IBDs were lower (ranging from 57.4 % to 65.0 %). Findings of this study show the potential of the VALORE network to provide enough exposure data to investigate the risk of serious infections for adalimumab, etanercept, and infliximab.